The relationship between Neutrophil to Lymphocyte Ratio (NLR), Platelet to Lymphocyte Ratio (PLR), and Monocyte to Lymphocyte Ratio (MLR) with the clinical severity level of COVID-19 patients at Udayana University Hospital (Research, Society and Development, 2024)
Background: COVID-19 is an pandemic with a high transmission rate. Due to its widespread availability, complete blood count has the potential to be used as an initial screening for clinical severity. Objective: This study aims to determine the relationship between NLR, PLR, and MLR with the clinical severity level of patients with COVID-19. Method: A cross-sectional study was conducted at Udayana University Hospital on COVID-19 patients hospitalized from March 2020 to March 2021. Subjects were divided into critical and non-critical groups and analyzed for their relationship with the components of the complete blood count on the first day of hospitalization. Result: The analysis found that the study subjects had a mean (± standard deviation) age of 54.20 (± 15.57) years. The mean (± SD) hemoglobin level was found to be 13.44 (± 4.05) g/dL, and the platelet count was 245.75 (± 107.36) x 103/μL. The median (interquartile range) leukocyte count was found to be 7.78 (4.91) x 103/μL, neutrophils 5.72 (4.91) x 103/μL, basophils 0.01 (0.01) x 103/μL, eosinophils 0.01 (0.01) x 103/μL, monocytes 0.53 (0.41) x 103/μL, lymphocytes 1.10 (0.89) x 103/μL, NLR 5.21 (7.77), PLR 193.34 (153.54), and MLR 0.51 (0.42). Conclusion: NLR, PLR, and MLR are significantly associated with the clinical severity level in COVID-19 patients at Udayana University Hospital. These findings can assist clinicians in assessing the potential for worsening clinical severity from mild to severe or critical levels in COVID-19 patients.